IDENTIFIKASI JENIS POHON JALUR HIJAU JALAN AHMAD YANI KOTA BANJARBARU - Mariano Alvarado Simamora; Susilawati Susilawati; Dina Naemah (Jurnal Sylva Scienteae, 2020)
This study aims to determine the type of trees along Jalan Ahmad Yani Banjarbaru City using census method. From the results of the research, it is known that the total of trees in Along Jalan Ahmad Yani Banjarbaru City consists of 389 trees consisting of 27 species, consisting of 6 types of fruits, and 21 species of wood. The most dominant tree found is Tanjung (Mimusops elengi)Keywords: Quality of Trees, Green Belt, Plants Health, Tree Species